Andexanet Alfa for Acute Major Bleeding Associated with Factor Xa Inhibitors - Connolly, Stuart J; Milling, Truman J; Eikelboom, John W; Gibson, C. Michael; Curnutte, John T; Gold, Alex; Bronson, Michele D; Lu, Genmin; Conley, Pamela B; Verhamme, Peter; Schmidt, Jeannot; Middeldorp, Saskia; et al. (The New England journal of medicine, 2016)
Andexanet alfa, a catalytically inactive decoy of factor Xa, successfully reversed the factor Xa inhibitory effects of rivaroxaban and apixaban in a small study involving patients with acute major bleeding. In randomized clinical trials, factor Xa inhibitors have been shown to be safe and effective for the treatment and prevention of venous thromboembolism and for stroke prevention in patients with atrial fibrillation. 1 – 4 However, factor Xa inhibitors have been associated with major and even fatal bleeding events. 1 – 4 Such episodes of acute major bleeding may be difficult to treat because there is no reversal agent. Andexanet alfa (andexanet) has been designed and developed specifically to reverse the effects of both direct and indirect factor Xa inhibitors. It is a recombinant, modified human factor Xa decoy protein that binds factor Xa . . .